Women's Protection Program Implementation in Donggala Regency - Nuraisyah Ambo (Fakultas Ilmu Sosial dan Ilmu Pendidikan Universitas Tadulako, 2022)
The goal of this research is to offer an overview of the Quality of Life and Women's Protection Program implementation in Donggala Regency. A qualitative research approach was employed. Secondary and primary data were employed, including descriptive qualitative data analysis. The findings of this study indicate that the Women's Protection Program was not properly implemented due to aspects of communication, resources, disposition, and bureaucratic structures that were not fully implemented due to insufficient human resources and infrastructure as a supporter in implementing the program, as well as poor coordination. Internal coordination (Coordination amongst Sectors in the Donggala Regency Family Planning and Women's Empowerment Agency) and external coordination (Relevant Regional Apparatus Work Units).